DAMPAK INDISIPLINER KETERLAMBATAN HADIR TERHADAP PROSES DAN HASIL ASESMEN KOGNITIF DI SMA PGRI 03 PALEMBANG - Cahya Murba, Seftian; Amelia Murba (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research examines how students’ lateness behavior influences the implementation process and outcomes of cognitive assessment at SMA PGRI 03 Palembang. A descriptive qualitative design was applied involving 30 students consisting of 25 male and 5 female participants. Findings revealed that frequent tardiness disrupted students’ mental preparedness and logical thinking processes, which subsequently affected their cognitive assessment performance, especially in critical reasoning tasks. Transportation limitations and ineffective time management were identified as dominant contributing factors, particularly among male students. To address this issue, the application of behavioral contract strategies within group guidance activities is proposed as an effort to strengthen discipline and enhance overall learning achievement.